Comparing the efficacy, safety, and satisfaction for moderate to severe glabellar frown lines between abobotulinum toxin A and incobotulinum toxin A: a multicenter randomized study - Jong Hun Lee; Seo Koo Lee; Sang Hun Kim; Sun Jae Lee; Jun Hyun Kim; Eun Soo Park (Archives of Aesthetic Plastic Surgery)
Background Botulinum toxin type A is widely used to improve facial wrinkles associated with aging, and various types are available. However, the efficacy, particularly the duration of effect, varies among these types, and research on this subject is limited. This study aimed to compare the efficacy and safety of incobotulinum toxin A and abobotulinum toxin A. Methods This prospective analysis included cases of moderate to severe glabellar lines treated with either incobotulinum toxin A or abobotulinum toxin A. After a 24-week follow-up, clinical photos were taken at each visit. The severity of the glabellar lines was evaluated by three groups: the investigator, the patients, and an independent evaluator. Results The study included a total of 42 patients. When comparing the improvement rates of glabellar lines at maximum frown for both groups at the week-4 visit, which was the primary efficacy endpoint, no statistically significant difference was observed. However, the abobotulinum toxin A group demonstrated a higher improvement at the week-24 visit, as evaluated by the investigator, and this difference was statistically significant. Conclusions Overall, the abobotulinum toxin A group exhibited a higher improvement rate in the glabellar lines at the frown state. The difference in the improvement rate at the week-24 visit was 36.86%, which was statistically significant.